Long-term renal function with cardiac contractility modulation therapy - Yücel, Gökhan; Yazdani, Babak; Schreiner, Kristin; Fastner, Christian; Hetjens, Svetlana; Husain-Syed, Faeq; Kruska, Mathieu; Dürschmied, Daniel; Krämer, Bernhard; Abraham, William T.; Akın, Ibrahim; Kuschyk, Jürgen (Cardiorenal Medicine, 2024)
Introduction: Cardiac implantable electrical devices are able to affect kidney function through hemodynamic improvements. The cardiac contractility modulation (CCM) is a device-based therapy option for patients with symptomatic chronic heart failure (HF) despite optimized medical treatment. The long-term cardiorenal interactions for CCM treated patients are yet to be described. Methods: CCM recipients (n = 187) from the Mannheim Cardiac Contractility Modulation Observational Study (MAINTAINED) were evaluated in the long-term (up to 60 months) for changes in serum creatinine, estimated glomerular filtration rate (eGFR), other surrogate markers of kidney function, and the chronic kidney disease (CKD) stage distribution. With regard to kidney function at baseline, the patients were furthermore grouped to either advanced CKD (aCKD, CKD stage ≥3, eGFR≤59 mL/min/1.73 m2, n = 107) or preserved kidney function and mild CKD (pCKD, CKD stages 1-2, eGFR≥60 mL/min/1.73 m2, n = 80). The groups were compared for differences regarding kidney function, New York Heart Association classification (NYHA), biventricular systolic function, HF hospitalizations and other parameters in the long-term (60 months). Results: CKD stage distribution remained stable during the entire follow-up (p = 0.65). An increase in serum creatinine (1.47 ± 1 vs. 1.6±1 mg/dL) with a corresponding decline of eGFR (58.2 ± 23.4 vs. 54.2 ± 24.4 mL/min/1.73 m2, both p < 0.05) were seen after 60 months but not before for the total cohort, which was only significant in pCKD patients in terms of group comparison. Mean survival (54.3 ± 1.3 vs. 55.3 ± 1.2 months, p = 0.53) was comparable in both groups. Improvements in NYHA (3.11 ± 0.46 vs. 2.94 ± 0.41-2.28 ± 0.8 vs. 1.94 ± 0.6) and LVEF (24.8 ± 7.1 vs. 22.9 ± 6.6-31.1 ± 11.4 vs. 35.5 ± 11.1%) were likewise similar after 60 months (both p < 0.05). The aCKD patients suffered from more HF hospitalizations and ventricular tachycardias during the entire follow-up period (both p < 0.05). Conclusions: The kidney function parameters and CKD stage distribution might remain stable in CCM treated HF patients in the long-term, who experience improvements in LVEF and functional status, regardless of their kidney function before. An impaired kidney function might be associated with further cardiovascular comorbidities and more advanced HF before CCM, and could be an additional risk factor of HF complications afterward.
Online veröffentlicht: 21. Juni 2024
Gesehen am 24.03.2025